Middle Management Leadership Experiences of a Mission-Driven Innovation University Strategy - Svend H. Christiansen; Xiangyun Du; Aida Olivia Pereira de Carvalho Guerra (MDPI AG, 2024)
This study explores academic middle managers' perspectives on a mission-driven university strategy in a Danish context, offering insights for institutions implementing similar strategies. The case of a Danish university highlights the vital role of academic middle managers in navigating strategic uncertainty. Success requires a nuanced understanding of organizational dynamics and aligning initiatives with institutional goals. The study, based on interviews with ten academic middle managers, reveals complexities and challenges associated with mission-driven innovation in higher education, through a phenomenographic and thematic analysis, concerning current impressions and experiences, the perceived barriers to implementation, and the perceived affordances of transforming into a mission-driven university. The findings emphasize the significance of overcoming internal resistance and establishing institutional support, providing valuable considerations for higher education institutions and their academic middle managers in implementing mission-driven innovation strategies, and have the potential to support the design and implementation of future higher education strategies for sustainability, pertaining to the responsibilities, interactions, and mediations across and among the upper management and the academic staff.